The Urgency of the Role of Amil Zakat in Laz Washal in the Welfare of the UMKM Society - Manna Wassalwa; Yenni Samri Juliaty Nasution (Penerbit Jurnal Indonesia, 2022)
The purpose of this paper is to find out how important the role of amil zakat in the amil zakat al washaliyah institution is. This study uses an approach based on library research. Management of zakat by the government includes the withdrawal of zakat (muzakki), collecting, registering, organizing, and finally distributing it to the rightful party. During the pandemic, the MSME community really needs the role of amil in the welfare of life. Amil Zakat must be creative, persistent, and honest, supported by government work and the right strategy so that zakat income will be higher.